2020
DOI: 10.1037/men0000239
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of respect, teacher–student relationships, and school climate among boys of color: A multifocus group study.

Abstract: Black and Latino students, particularly boys, experience higher rates of school disengagement and dropout than their non-Hispanic White peers (Gregory, Skiba, & Noguera, 2010). Although attention to exclusionary disciplinary practices is necessary to understand their disengagement, a focus on the experiences and perceptions of relationships and on teacher attitudes among boys of color can help to illuminate some of the challenges they experience. Eight focus groups involving 23 middle school-and 99 high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The formation of school climate is complex and can be the result of multiple influences at the proximal and distal levels of the educational system. The characteristics of students, teachers, and staff can be considered as factors related to the internal development of school climate [ 11 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of school climate is complex and can be the result of multiple influences at the proximal and distal levels of the educational system. The characteristics of students, teachers, and staff can be considered as factors related to the internal development of school climate [ 11 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of characters with respect is the main part that teachers must do and familiarize themselves with. Because respect for the teacher is a noble quality that brings glory to students and makes them love their lessons (Balyer, 2019;Liang et al, 2020;Zhou et al, 2020). The formation of students' Islamic behavior begins with paying attention to the strength of the soul in humans, namely the power of hammiya or called anger turmoil.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Jia et al's (2016) study, Liang et al (2019) examined the impact of school climate among boys of color and barriers to academic success. In this study, the researchers interviewed eight focus groups of Black male students to determine what factors affected their schooling.…”
Section: School Climatementioning
confidence: 93%
“…The first theme to emerge was school climate, which suggested that school climate is a perceived barrier among this student subgroup. Liang et al (2019) further stated that Black and Latino students were more affected by poor school climate and dropped out of high school more than White students. These findings support that school climate may play a critical role in a student's decision to drop out of school, specifically with marginalized student populations.…”
Section: School Climatementioning
confidence: 99%